2020
DOI: 10.3390/pathogens9121007
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characteristics of Extended-Spectrum β-Lactamase-Producing Escherichia coli from Dairy Cattle, Milk, and Farm Environments in Peninsular Malaysia

Abstract: The emergence and spread of antimicrobial resistance genes and resistant bacteria do not recognize animal, human, or geographic boundaries. Addressing this threat requires a multidisciplinary approach involving human, animal, and environmental health (One Health) sectors. This is because antimicrobial agents used in veterinary medicine have been reported to be the same or similar to those in human medicine use. Extended-spectrum β-lactamase (ESBL) E. coli is a growing public health problem worldwide, and the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 32 publications
3
35
0
1
Order By: Relevance
“…In 15 samples, E. coli -originated contigs harboured the gene TEM-116 . Plasmid origin is a common feature of ESBL genes such as TEM-116 according to several publications and is often referred to as a feature to facilitate their quick spread [ 91 , 92 , 93 ]. In the E. coli isolate sample s15, one contig had the marA and marR genes.…”
Section: Discussionmentioning
confidence: 99%
“…In 15 samples, E. coli -originated contigs harboured the gene TEM-116 . Plasmid origin is a common feature of ESBL genes such as TEM-116 according to several publications and is often referred to as a feature to facilitate their quick spread [ 91 , 92 , 93 ]. In the E. coli isolate sample s15, one contig had the marA and marR genes.…”
Section: Discussionmentioning
confidence: 99%
“…These authors were able to confirm the bla ESBL genes transferred by conjugation as bla CTX-M-14 , bla CTX-M-15 , and bla TEM-20 . Others have used the two-step approach, as we did in this study, to identify and confirm ESBL producing E. coli [ 11 , 17 , 38 , 39 ]. Other studies have also found low numbers of ESBL producing E. coli in farm animals.…”
Section: Resultsmentioning
confidence: 99%
“…All isolates classified as intermediate or resistant using CLSI criteria (≤17 mm) to cefoxitin were suspected to be AmpC producers [ 36 ]. Based on the results of the phenotypic test, strains designed as putative ESBL producers were further analyzed by PCR for genes encoding ESBL genotypes: TEM, OXA, SHV, and CTX-M [ 37 , 38 , 39 , 40 , 41 ]. A strain of ESBLs-producing Klebsiella pneumoniae (ATCC 700603) was used as positive control for ESBLs gene screening as well as standard strain Escherichia coli (ATCC 25922).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid origin is a common feature of ESBL genes such as TEM-116 according to several publications and is often referred to as a feature to facilitate their quick spread. [74][75][76] In the E. coli isolate sample s15, one contig had the marA and marR genes. These widespread multiple antibiotic resistance genes had been identified on plasmids before.…”
Section: Discussionmentioning
confidence: 99%